Audit Fee as Mediation Effect of Company Size, Complexity of the Company and Independent Commissioners on Audit Quality - Diffa, Diffa Ayomi Mayapa; Taqi, Muhamad (Accounting and Sustainability, 2024)
The purpose of this research is to determine audit quality. There are three independent variables, namely company size, company complexity and also independent commissioners; the dependent variable is audit quality and the mediator variable is audit fees. This research is quantitative. This research uses secondary data in the form of financial reports and annual reports on the Indonesia Stock Exchange (BEI). The main population of this research is financial sector companies listed on the Indonesia Stock Exchange from 2018 to 2023. The purposive sampling method was used to form the research sample. For six consecutive years, 174 companies from the financial and banking sector were included in the sample. Data was processed with SPSS v25. Logistic regression and path analysis and using the Sobel online calculator. The results of this research indicate that company size and complexity do not affect audit quality, independent commissioners influence audit quality in a negative way; company size and company complexity influence in a positive way; and audit fees do not affect audit quality.